Cultural Differences in Emotion Suppression in Belgian and Japanese Couples: A Social Functional Model - Schouten, Anna; Boiger, Michael; Kirchner-Häusler, Alexander; Uchida, Yukiko; Mesquita, Batja (Frontiers in Psychology, 2020)
Emotion suppression has been found to have negative psychological and social consequences in Western cultural contexts. Yet, in some other cultural contexts, emotion suppression is less likely to have negative consequences; relatedly, emotion suppression is also more common in those East-Asian cultural contexts. In a dyadic conflict study, we aim to (a) conceptually replicate cultural differences found in previous research with respect to the prevalence and consequences of emotion suppression, and (b) extend previous research by testing whether cultural differences are larger for some than for other types of negative emotions. We postulate that cultural differences in suppression are less pronounced for socially engaging emotions (e.g., guilt) than socially disengaging emotions (e.g., anger), because the former foster the relationship, whereas the latter emphasize individual goals. Belgian (N=58) and Japanese (N=80) couples engaged in a 10-minute conflict interaction followed by video-mediated recall, during which participants rated their emotions and emotion suppression every 30 seconds. As predicted, Japanese participants reported more suppression than their Belgian counterparts, but the cultural difference was more pronounced when participants experienced more socially disengaging emotions than when they experienced more socially engaging emotions. These results suggest that the type of emotion should be considered when describing cultural differences in emotion suppression. Finally, and consistent with previous research, emotion suppression was negatively associated with interaction outcomes (i.e. conflict resolution) in Belgian couples, but not in Japanese couples.